Laser ultrasonic time-domain synthetic aperture focusing (SAFT) co-overlay software and hardware (COSH) computing system based on ZYNQ - Tan, Junfu; Ni, Chenyin; Wu, Chanjuan; Ying, Kaining; Dai, Lunan; Shen, Zhonghua (Frontiers in Materials, 2024)
The application of laser ultrasonic technology to defect detection is being widely studied. The Synthetic Aperture Focusing Techniques (SAFTs) is one of the imaging algorithms for detecting and imaging internal defects. SAFT based on Delay and Sum (DAS-SAFT) is known for high-quality imaging results. However, it has the disadvantages of the large calculation amount, which severely restricts its application. This work proposes a Co-Overlay Software and Hardware method (SAFT-COSH) based on Zynq, which uses parallelism and pipeline technology on FPGA and can efficiently accelerate DAS-SAFT operations. It can be found that the result obtained by the SAFT-COSH method is similar to the original method. Moreover, the time consumption of the SAFT-COSH system is 1/28 of that of the I9-13900KF CPU used for DAS-SAFT calculation. Finally, it was found by analyzing the time consumption of the DAS-SAFT procedure that the time consumption of SAFT-COSH system is short enough to support real-time 3D defect imaging. Characteristics of high efficiency and low cost in the SAFT-COSH method make it applicable in fields that require fast imaging using SAFT-based methods.